A forgotten pleasure: A unique case report of a neglected foreign body in a postmenopausal woman with persistent vaginal discharge - Muhammad Amir Nazri; Wan Mohd Nazlee Wan Zainon; Shaiful Bahari Ismail (Malaysian Family Physician, 2025)
Recurrent vaginal discharge is a significant health issue for women globally, often leading to discomfort and a reduced quality of life. While normal vaginal discharge helps maintain vaginal health, changes in its composition can signal underlying conditions requiring prompt assessment and treatment. The causes of recurrent vaginal discharge are diverse, including infections, hormonal changes, and anatomical factors. Common infections like bacterial vaginosis, vulvovaginal candidiasis, and trichomoniasis are frequently encountered, with studies estimating that up to 75% of women will experience vulvovaginal candidiasis at least once in their lifetime. Non-infectious causes, such as foreign bodies, vaginal atrophy, and cervical or endometrial anomalies, also contribute but are less commonly addressed. Despite its prevalence, diagnosing recurrent vaginal discharge can be challenging, requiring a thorough approach. Cultural taboos and stigma surrounding vaginal health may discourage women from seeking medical help, potentially delaying diagnosis and treatment. This article reports a case of a vaginal foreign body presenting with persistent discharge and emphasizes the importance of a comprehensive approach to diagnosing and managing vaginal discharge.